A Study on Four-Bar Mechanism with Constant Coupler Point Velocity: Modelling, Numerical Simulation and Experimental Application - Hülako, Halit; Çakar, Orhan (My University, 2025)
In industry, the trace path of a point on the coupler link of four-bar mechanism is often utilized and sometimes it is desired that the couplar point moves on its path with constant velocity. This can be achieved by the variable crank speed. Processes requiring constant speed are often achieved by designing expensive complex mechanisms with high degrees of freedom without feedback control. This study considers the four-bar mechanism driven by a DC motor with constant coupler point velocity. Matlab Simscape MultiBody tool is used to model and to simulate the system dynamics. For the first time, we have successfully implemented an experimental application of coupler point speed control, a mechanism that is much needed in the industry, at a remarkably low cost. We developed a highly detailed simulation model that incorporates intricate system dynamics, including bearing frictions. Additionally, we accurately predicted crucial motor parameters for the application through cost-effective estimation techniques. In order to show the efficiency of the method, some experimental case studies are made besides the numerical simulations, and the results are compared. PID algorithm is used to control of the crank speed and it is shown that the desired couplar point velocity is achieved.
Keywords: Four-Bar Mechanism; Crank Speed Control; Simscape Multibody Model; Coupler Point